Kehidupan Sosial Ekonomi Pappalimbang Di Sungai Jeneberang Kabupaten Gowa (1985-2020) - Mardiana Mardiana; Andi Ima Kesuma; Bahri Bahri (Phinisi Integration Review, 2022)
The study aims to discover; 1) The dynamics of Pappalimbang on Jeneberang River, 2) The Socio-Economic Life of Pappalimbang on the Jeneberang River. The type of this study is historical research with a sociological approach. The historical method used to discover the track record of Pappalimbang Socio-Economic life on Jeneberang River in Gowa district in 1985-2020 by interviewing various sources. The results of the study reveal that 1) The dynamics of Pappalimbang progressed and developed over time, which used to only use bamboo that was linked together and used oars, now it uses an engine, and the boat is made of special wood where the two boats are put together so they can load motorcycles. 2) The Socio-Economic life of the Taeng Village community tends to be influenced by Pappalimbang activities. Pappalimbang helps residents get jobs with sufficient wages to meet their needs, and their daily activities have many interactions in Pappalimbang because the Taeng Village community and its surroundings are very dependent on Pappalimbang so people can avoid congestion.